2023
DOI: 10.3389/fimmu.2023.1174762
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a novel cuproptosis-related stemness signature to predict prognosis and immune landscape in lung adenocarcinoma by integrating single-cell and bulk RNA-sequencing

Abstract: BackgroundCancer stem cells (CSCs) play vital roles in lung adenocarcinoma (LUAD) recurrence, metastasis, and drug resistance. Cuproptosis has provided a novel insight into the treatment of lung CSCs. However, there is a lack of knowledge regarding the cuproptosis-related genes combined with the stemness signature and their roles in the prognosis and immune landscape of LUAD.MethodsCuproptosis-related stemness genes (CRSGs) were identified by integrating single-cell and bulk RNA-sequencing data in LUAD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Upregulation of the C4BP gene as an inhibitor of the complement system is a possible strategy adopted by the tumor cells to evade the immune system [32] . Constructed a risk score based on the 129 intersecting differentially expressed genes by LASSO and univariate regression, it was found that the higher expression of C4BPA, the lower the overall survival rate of lung adenocarcinoma patients [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of the C4BP gene as an inhibitor of the complement system is a possible strategy adopted by the tumor cells to evade the immune system [32] . Constructed a risk score based on the 129 intersecting differentially expressed genes by LASSO and univariate regression, it was found that the higher expression of C4BPA, the lower the overall survival rate of lung adenocarcinoma patients [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, how to detect the intensity of cuproptosis and how to assess the effects of genes on cuproptosis are the other critical issues needed to be addressed. Regretfully, several recent studies in Frontiers in Immunology have failed to eliminate the above-mentioned concerns well (3)(4)(5). Therefore, we performed the following discussion which aims to provide some insights into further CR research.…”
Section: Introductionmentioning
confidence: 98%
“…Accurate prediction of patients' prognosis plays a crucial role in providing beneficial treatment decisions and improving patients' quality of life. Currently, several LUAD prognostic models have been developed, including the basement membrane‐related gene prognostic model, 6 lipid metabolism‐related gene prognostic model, 7 hypoxia‐related gene prognostic model, 8 cuproptosis‐related feature prognostic model, 9 and antigen‐presenting cell/T/NK cell‐related gene prognostic model, among others. Although these existing LUAD prognostic models have provided useful information for predicting patient survival and prognosis assessment, they still have significant limitations as a result of issues such as small sample sizes, disease heterogeneity, and model feasibility.…”
Section: Introductionmentioning
confidence: 99%